'Corps a corps': Martyrs, Models, and Myths in Harriet Hosmer's Beatrice Cenci. Issue 4 (5th August 2021) - Gustin, Melissa L.
Abstract : This essay demonstrates that Harriet Hosmer's Beatrice Cenci (1855–56) not only illustrated a popular literary narrative, but also responded to specific Roman historic, cultural and artistic touchstones as a performance of romanità through visual literacy. It addresses and challenges the accretion of historical myths around Hosmer's sculpture, its models, and its modern interpretations through the written and visual sources available to her in the nineteenth century. I draw attention to the conflation of key historic events in Rome, the execution of Beatrice Cenci, and the production of Stefano Maderno's Saint Cecilia . These narrative parallels and an emphasis on identifiable women's bodies has led to scholarship repeating the rumour of Hosmer's aristocratic model, which I demonstrate is problematic for evidentiary and interpretative reasons. The essay argues that a scholarly emphasis on her biography and psychology as a queer woman has ignored the sophisticated visual and historic citations in her sculpture.